PERBANDINGAN HASIL PEMERIKSAAN MIKROSKOPIS BASIL TAHAN ASAM METODE DEKONTAMINASI DENGAN METODE TES CEPAT MOLEKULER - Nurul Husna; Novi Utami Dewi (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
Tuberculosis (TB) remains a serious public health problem because of its high potential for person-to-person transmission. Sputum examination using NaOH 4% has a higher sensitivity compared to direct acid-fast basilli smear that has a sensitivity 64.8% and 30%, respectively. New methods have been widwly developed for rapid detection and identification of Mycobacterium tuberculosis (MTB) in  active tuberculosis with the best techniques such as genomic or molecular examination. An automated molecular testing for Mycobacterium tuberculosis identification has a similar sensitivity with culture as gold standard method. The aim of this study to compare the results between microscopic examination of acid-fast bacilli decontamination method and molecular examination. This study is a comparative study with cross sectional approach which held in Microbiology Laboratory of Center of Lung Health of Makassar. The results of the acid-fast bacilli decontamination and the molecular method have diagnostic result statisticaly analysis showed no significant difference.